Business Negotiation Approach Model and Strategy for Community Leaders in Resolving Land Dispute Conflicts in Maluku Province - Fransiska Ralahallo; Aris Firmansyah (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This study was written with the aim of knowing and describing how the Model Approach and Negotiation Strategy of Community Leaders in Resolving Land Dispute Conflicts in Marafenfen Village, Aru Islands, Maluku Province Community leaders are parties who have advantages over the general public and play an important role in making decisions. Land dispute conflicts that occurred in the village of Marafenfen are social conflicts that often occur considering the people who do not really understand the rights to the land they want to own. This article is an article that uses a qualitative descriptive method, namely research that seeks to describe or describe the object under study based on the facts in the field. then the data analysis technique used in this study is qualitative data analysis, The results of the research obtained by the author can be concluded that in resolving land disputes, community leaders use Competitive Approach Model but some community leaders do not understand the Negotiation processes so they still have not found an agreement.